TRANSFORMASI SIMBOLIK HOMOSEKSUAL DI TELEVISI (Sebuah Studi Analisis Semiotika Barthes dan Semiotika Sosial M.A.K. Halliday dalam Program CS: File Kompas TV) - Altobeli Lobodally (SEMIOTIKA: Jurnal Komunikasi, 2014)
As an audio-visual medium, television has a view majesty tasks. Television is a medium to informed, educated, to entertained, and a medium to transformed the value of life. But the magic box, has a great power. Television has a power to create a new history and to reduce cognition for public. And it is happen to homosexsual too. By the Crime Story (CS): File programmes, Kompas TV constructed people mind that homosexual is a huge moral panic. Because of homoseksuality has pictured as an abnormal behavior, psycopat, and a sinner. From the semiotic and social semiotic as a methodology, the pictured of homosexuality has been construted to the public mind. The CS: File crew has been transformed the homosexuality as a television show. The homosexuality shows as an abnormal behavior, psycopatic, a sinner, and also a criminal. From the shows, the capitalist as a dominant class has been dominated homoseskuality. The television holly tasks as mass media, has been transformed to the capitalist tribute.Keywords: Symbolic Transformation, Gay, Television, Semiotics, Programme